Perioperative and Long-Term Development of Anxiety and Depression in CABG Patients - Korbmacher, B.; Ulbrich, S.; Dalyanoglu, H.; Lichtenberg, A.; Schipke, J. D.; Franz, M.; Schäfer, R. (The Thoracic and Cardiovascular Surgeon, 2013)
Background The high incidence of symptomatic anxiety and depression in coronary artery bypass graft (CABG) patients may lead to impaired quality of life and increased morbidity and mortality. This prospective longitudinal study on CABG patients should provide data for future preoperative and postoperative psychotherapeutic interventions.Methods From 2009 to 2010, 135 consecutive patients who were able and prepared were consulted by one interviewer immediately before 1 week (early) and 6 months (late) after surgery to complete the “Hospital Anxiety and Depression Scale” questionnaire.Results Compared with the standard population, anxiety scores (AS) were preoperatively elevated in 39.3% of the patients. Early and late after surgery, AS had decreased to 34.4% (not significant [n.s.]) and 28.9% (p < 0.01).Before surgery, depression scores (DS) were elevated in 20.7%. Early and late after surgery, DS further increased to 24.0% (n.s.) and 28.0% (n.s.).Preoperative elevated DS appeared to correlate with increased complications. Mortality was not associated with elevated AS or DS. Both scores were not affected by on- or off-pump surgery.Conclusion Remarkably high AS and elevated DS late postoperatively require psychotherapeutic support even after seemingly successful CABG.
Keywords: perioperative anxiety/depression; postoperative morbidity; CABG; psychotherapeutic screening/intervention